Two percent dehydration impairs and six percent carbohydrate drink improves boys basketball skills - Dougherty, K. A.; Baker, L. B.; Chow, M.; Kenney, W. l. (Medicine & Science in Sports & Exercise, 2006)
Purpose: To determine the effects of exercise heat-induced two percent dehydration (DEH) and euhydration (EUH) with a six percent carbohydrate-electrolyte solution (CES) compared with placebo EUH (P EUH) on basketball skills in skilled young players.